ECONOMI VALUE ADDED OF BLUE SWIMMING CRAB (Portunus pelagicus) PROCESSING AT CV. LAUT DELI BELAWAN NORTH SUMATERA - Angel Zesikha Purba; Lamun Bathara; Darwis ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted on May 2016 at CV. Laut Deli Belawan North Sumatera . The method used is survey method . Based on the research that has been done toward the Economic Value added of blue swimming crab processing consist of steam crab and meat crab. There are 7 various and its percentage, such as jumbo (12,5 %), flower as (12,5 %), special (12,5%), backfin (12,5%), and there other produt of claw meat (red meat) such as claw fingger (16,67%), leak meat (16,67 %), and secound grade (16,67 %). Value added of blue swimming crab (Portunus pelagicus) at westerly period (time of scarcity before harvest) amount Rp 51.189.500/month and value easterly period amount Rp 71.706.400/month. Keywords : Value Added, Processing, Blue Swimming Crab